Cardiac troponin T does not increase after electrical cardioversion for atrial fibrillation or atrial flutter. Issue 3 (1st September 1998) - Greaves, K; Crake, T
Abstract : Objective: To determine whether cardiac troponin T increases after electrical cardioversion in patients with atrial fibrillation or atrial flutter. Design: Serum creatine kinase (CK), creatine kinase-MB (CKMB), and cardiac troponin T were measured before, 24 hours, and 48 hours after cardioversion in 15 patients with atrial fibrillation or atrial flutter. Results: 12 of the 15 patients (80%) were successfully cardioverted to sinus rhythm. The median number of shocks was three (range one to six), the median cumulative energy 710 J (50 to 1430 J), and the median peak energy 300 J (50 to 360 J). Total CK increased from a baseline median concentration of 92 (45 to 259) to 1324 (96 to 6660) U/l at 24 hours and 1529 (120 to 4774) U/l at 48 hours after cardioversion. There was a small increase in CKMB but the ratio of CKMB to CK did not increase. There was no increase in cardiac troponin T in any patient. Conclusions: Following electrical cardioversion of atrial fibrillation or atrial flutter, cardiac troponin T remains unchanged despite a large rise in total CK, indicating that the CK is derived from skeletal muscle and that myocardial injury does not occur. If cardiac troponin T is increased after cardioversion for atrial arrhythmias then other causes of myocardial damage should be sought.